Hubungan Intensitas Bermain Game Online Dengan Hasil Belajar Siswa Pada Mata Pelajaran IPA Kelas VIII di SMP Negeri 18 Model Palu - Wulandari; Kundera, I Nengah; Lilies; Laenggeng, Abd. Hakim; Fardha, Rizka; Ashari, Abd. (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study aims to determine the relationship between the intensity of playing online games and student learning outcomes in science subjects in grade VIII at SMP Negeri 18 Model Palu. This type of research uses quantitative research with correlation analysis. The sample of this study is class VIII which totals 105 students. The data collection technique in this study is a questionnaire. The results of this study showed that the intensity of playing online games obtained in the medium category was 65 students (61.90%), the high category was 27 students (25.71%), and the low category was 13 students (12.38%). The number of hours used in one play was obtained more than 5 hours by 32 students (55.17%), up to 3 hours by 18 students (31.03%), and up to 1 hour by 8 students (13.79%). The results of bivariate analysis, it showed a correlation coefficient (Spearman's rho) of 0.106, there was a positive but very weak relationship between the intensity of playing online games and student learning outcomes. With a significance of 0.282, because it is 0.282>0.05, it is concluded that there is no significant relationship between the intensity of playing online games and student learning outcomes in science subjects in grade VIII at SMP Negeri 18 Model Palu.